2019
DOI: 10.1016/j.enbuild.2019.109435
|View full text |Cite
|
Sign up to set email alerts
|

Use of adaptive control and its effects on human comfort in a naturally ventilated office in Alameda, California

Abstract: Naturally ventilated buildings have been found to be comfortable over a wider range of indoor temperatures than in air-conditioned buildings, while using less energy. The mechanisms underlying this are not well understood. Through a longitudinal field study of a naturally ventilated office in Alameda, CA, we obtained insights into how occupants exercise various adaptive control opportunities to meet their comfort needs in the absence of a mechanical HVAC system. Continuous measurements were made of adaptive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A review paper [38] and a field study of a fan-cooled office [39] have demonstrated successful uses of ceiling fans. Office workplace cooling is particularly demanding because people may not be at liberty to move their location, and the fans may be only under group, rather than individual, control.…”
Section: Room Airflow Under Ceiling Fansmentioning
confidence: 99%
“…A review paper [38] and a field study of a fan-cooled office [39] have demonstrated successful uses of ceiling fans. Office workplace cooling is particularly demanding because people may not be at liberty to move their location, and the fans may be only under group, rather than individual, control.…”
Section: Room Airflow Under Ceiling Fansmentioning
confidence: 99%